2011
DOI: 10.1097/cej.0b013e328345f971
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated pesticides and cancer of the head and neck

Abstract: Cancer of the head and neck is a pervasive problem with recognized determinants including tobacco use, alcohol consumption, and earlier radiation exposure. Organochlorine pesticides (OCPs) have been shown to have carcinogenic potential in both animals and humans. OCPs have previously been widely used in the agricultural industry of rural Oklahoma. Seven patients from rural Oklahoma with head and neck cancer and without any of the usual risk factors were tested for the presence of OCPs in their adipose tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this respect, the use of various pesticides canresult into wide range of human diseases and adversely impact the health and quality of life of humans (Nasterlack, 2001). Recent reports have revealed that pesticides may cause liver, pancreas, brain, prostate and other cancers due to their inherent toxicity in human (Koutros et al, 2013;Boada et al, 2012;Liu, 2012;Giannandrea, 2012;Govett et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the use of various pesticides canresult into wide range of human diseases and adversely impact the health and quality of life of humans (Nasterlack, 2001). Recent reports have revealed that pesticides may cause liver, pancreas, brain, prostate and other cancers due to their inherent toxicity in human (Koutros et al, 2013;Boada et al, 2012;Liu, 2012;Giannandrea, 2012;Govett et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that contamination with chlorinated pesticides can be related to neurodegenerative diseases and cancers and contribute to the development of type 2 diabetes mellitus (T2D), due to the interference in glucose uptake and adiposity function, resulting in proinflammatory responses and disrupted energy metabolism [ 9 , 10 , 11 ]. These substances can follow the transplacental route, and be transferred through lactation; therefore, individuals can be exposed to these compounds before birth and in early childhood [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…hepatocellular carcinoma (Zhao et al, 2011), breast cancer (Salehi et al, 2008), cancer of the head and neck (Govett et al, 2011), non-Hodgkin lymphoma (Engel et al, 2007), prostate cancer (Xu et al, 2010), testicular germ cell tumors (McGlynn et al, 2008), or pancreatic cancer (Hardell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been conflicting reports on the relationship between exposure to low levels of POPs, such as those occurring in the general population, and cancer risk, with some studies reporting positive associations but many others finding no evidence to support a causal association (Cassidy et al, 2005;Charlier et al, 2003;Cohn et al, 2010;Gatto et al, 2007;Govett et al, 2011;Hardell et al, 2006;Hoyer et al, 2001;Laden et al, 2001;Lopez-Carrillo et al, 2002;Lopez-Cervantes et al, 2004;Mozzachio et al, 2008;Pavuk et al, 2004;Recio-Vega et al, 2011;Snedeker, 2001;Soto and Sonnenschein, 2010;Svensson et al, 1995;Ward et al, 2000;Wolff et al, 2000;Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%